Digital Evidence under the Indian Legal System – Study of Problems and Perspective - Raj Goyal, Himani; Prasad Mali, Mahaveer (Journal of Neonatal Surgery, 2025)
The proliferation of digital technologies has reshaped the evidentiary landscape in India, where electronic records now play a decisive role in criminal prosecutions, civil disputes, and commercial litigation. The Indian Evidence Act, 1872, as supplemented by the Information Technology Act, 2000, laid the foundation for the admissibility of electronic records, but persistent interpretative challenges particularly surrounding Section 65B certificates led to judicial uncertainty until the Constitution Bench ruling in Arjun Panditrao Khotkar. The recent enactment of the Bharatiya Sakshya Adhiniyam, 2023, seeks to modernize evidentiary law by refining procedural rules for digital records, yet difficulties remain in ensuring authenticity, reliability, and due process safeguards. This paper critically examines the concept and nature of digital evidence, statutory provisions under the IEA and BSA, and judicial interpretations shaping its admissibility. It highlights key problems such as tampering risks, inadequate forensic infrastructure, cloud and cross-border data challenges, and privacy concerns in light of Puttaswamy. The study further evaluates the evidentiary value of expert opinion, chain of custody principles, and international best practices. Finally, it proposes reforms including blockchain-based authentication, a Digital Evidence Authority, judicial training, and enhanced global cooperation, arguing for a balanced regime that integrates technological innovation with constitutional safeguards in digital justice delivery